Sri Ramakrishna Paramahansa - Paṇḍayā, Dushyanta 1916- (New Delhi Readworthy Publ., 2008)
On the life and achievements of Ramakrishna, 1836-1886, Hindu religious leader from Bengal, India
Includes index. - Includes bibliographical references
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Ramakrishna 1836-1886; Ramakrishna Mission -- Biography; Hindus -- Biography -- India